Cytotoxic Th1 and Th17 cells infiltrate the intestinal mucosa of Behcet patients and exhibit high levels of TNF-α in early phases of the disease. Issue 49 (December 2016) - Emmi, Giacomo; Silvestri, Elena; Bella, Chiara Della; Grassi, Alessia; Benagiano, Marisa; Cianchi, Fabio; Squatrito, Danilo; Cantarini, Luca; Emmi, Lorenzo; Selmi, Carlo; Prisco, Domenico; D'Elios, Mario Milco
Abstract: Background: Gastrointestinal involvement is one of the most serious in Behçet disease, potentially leading to severe complications. Aim of this study was to investigate at mucosal level the T-cell responses in Behçet patients with early intestinal involvement. Methods: We isolated T cells from intestinal mucosa of 8 patients with intestinal symptoms started within 6 months. T lymphocytes were cloned and analyzed for surface phenotype and cytokines production. Results: We obtained 382 T-cell clones: 324 were CD4+ and 58 were CD8+. Within the 324 CD4+ clones, 195 were able to secrete IFN-γ and TNF-α, but not IL-4, nor IL-17 thus showing a polarized Th1 profile, whereas CD4 clones producing both IFN-γ and IL-17 (Th1/Th17 profile) were 79. Likewise, the number of CD8 clones producing type 1 cytokines was higher than those of CD8 clones producing both type 1 and 2 cytokines. Almost all intestinal-derived T-cell clones expressed perforin-mediated cytotoxicity and Fas–Fas Ligand-mediated pro-apoptotic activity. Conclusions: Our results indicate that in the early stages of the disease, both Th1 and Th17 cells drive inflammation leading to mucosal damage via abnormal and long-lasting cytokines production as well as via both perforin- and Fas–Fas ligand-mediated cytotoxicity. Finally, all the T cells at mucosal level were able to produce large amount of TNF-α, suggesting that its production is a property of intestinal T cells of patients with early active intestinal disease. These results support the therapy with anti-TNF-α agents and suggest the use of anti-IL-17 monoclonal antibodies in Behçet patients with early intestinal involvement.